Lipopolysaccharides Inhibit REG3A Self-Aggregation on Gold Nanoparticles A Combined Study of Multivariate Analysis on Time-Resolved Localized Surface Plasmon Resonance Spectra and Molecular Modeling - Han, Zhenxin (Langmuir : the ACS journal of surfaces and colloids, 2019)
Aggregation behavior of proteins on the surface of gold nanoparticles (AuNPs) has been extensively studied for its promising applications in biosensing, bioimaging, photodynamic therapy, drug delivery, etc. In this work, we studied adsorption kinetics of an antimicrobial protein, regenerating islet-derived protein 3-alpha (REG3A), on the surface of as-synthesized citrate-capped AuNPs under the influence of lipopolysaccharides (LPSs), with a combined method of UV-vis spectroscopy, multivariate analysis, and molecular dockings. In the AuNPs-REG3A binary system, a component with an "up-and-down" signal was detected by the in-depth data analysis on time-resolved spectroscopic data, corresponding to the protein agglomeration and exfoliation observed in transmission electron microscopy and atomic force microscopy experiments. Intriguingly, LPSs can rescue the spectral oddity-the adsorption pattern in the AuNPs-REG3A-LPS ternary system becomes normal and similar to a typical single-layer mode as in our previous study of the serum albumin-AuNP system ( Ren , X. ; et al., Spectrosc. Lett. , 2016 , 49 , 434 - 443 ). The following molecular modeling suggests that LPS molecules mainly interact with three segments of REG3A amino acid sequences, i.e., P109-T110-Q111-G112, P115-N116, and P137-S138-T139. The latter two protein-ligand interactions impair the REG3A-REG3A protein-protein interaction between the two subunits (E114-P115-N116-G117-E118 and N136-P137-S138-T139-I140). Thus, our results elucidate the LPS inhibitory effect on fibrous protein self-aggregation at the AuNP surface, and molecular dockings give a plausible mechanism to rationalize the competition among protein-protein and protein-ligand interactions